2005
DOI: 10.1074/jbc.m411392200
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-associated Herpesvirus Activation of Vascular Endothelial Growth Factor Receptor 3 Alters Endothelial Function and Enhances Infection

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV; also known as human herpesvirus 8) is the etiologic agent of Kaposi's sarcoma, an endothelial neoplasm. This ␥-herpesvirus encodes for several unique proteins that alter target cell function, including the virion envelope-associated glycoprotein B (gB). Glycoprotein B has an RGD (Arg-Gly-Asp) motif at the extracellular amino terminus region and binds to the ␣ 3 ␤ 1 surface integrin, which enhances virus entry. We now report that gB can activate the vascular endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…In addition, the ability of KSHV-gB⌬TM to induce FAK in HFF was inhibited by preincubating gB with ␣3␤1 integrin. Incubation of HMVEC-d with KSHV-gB⌬TM, but not KSHV-gB⌬TM-RGA, induced the phosphorylation of VEGFR-3 in HMVEC-d, and ␣3 was detected with immunoprecipitation by anti-VEGFR-3 antibodies in gB-treated endothelial cells (90). In addition, the results shown here demonstrate the specific association of ␣3␤1 integrin with CD98/xCT molecules in the infected cells.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, the ability of KSHV-gB⌬TM to induce FAK in HFF was inhibited by preincubating gB with ␣3␤1 integrin. Incubation of HMVEC-d with KSHV-gB⌬TM, but not KSHV-gB⌬TM-RGA, induced the phosphorylation of VEGFR-3 in HMVEC-d, and ␣3 was detected with immunoprecipitation by anti-VEGFR-3 antibodies in gB-treated endothelial cells (90). In addition, the results shown here demonstrate the specific association of ␣3␤1 integrin with CD98/xCT molecules in the infected cells.…”
Section: Discussionsupporting
confidence: 52%
“…To support these transcriptional studies, ELISAs were performed to determine the levels of VEGF, a downstream target of HIF-1␣, which was previously demonstrated to be induced by KSHV infection (21,47). The data obtained from cells transiently expressing LANA showed that the levels of VEGF produced were also significantly increased in HEK293T cells transfected with LANA compared to only HIF-1␣ expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cells express- ing VEGFR-3 are slightly more infectible by KSHV, suggesting that the upregulation of lymphatic markers could enhance viral infection or reinfection, which may be required for the maintenance of KSHV latency (58,63). However, VEGFR-3 is neither necessary nor sufficient for viral entry.…”
Section: Discussionmentioning
confidence: 99%